Analysis of Students’ Reading Interests in Grade IV of SDN Dawuan Tengah 6 - Putri Ayu Sholihah; Anggy Giri Prawiyogi; Sinta Maria Dewi (MASI Mandiri Edukasi, 2026)
The low interest in reading among elementary school students is a serious challenge in education, especially amid the onslaught of digital media. This study aims to analyze the level of interest in reading and the factors that influence it among fourth-grade students at SDN Dawuan Tengah 6. The research method used is a descriptive qualitative method. Data collection techniques were carried out through direct observation in class, distributing questionnaires to students, and interviews with fourth-grade teachers. The results of the study indicate that fourth-grade students’ interest in reading is in the [specify: e.g., medium/low] category. Supporting factors for reading interest include the availability of interesting reading materials and teacher support. Meanwhile, inhibiting factors found include dependence on gadgets, a lack of diversity in the book collection in the reading corner, and a lack of reading habits in the family environment. The conclusion of this study is the need for innovation in reading corner management and more interactive literacy strategies to increase students’ reading enthusiasm from an early age.